Upaya Edukasi Anti Bullying Pada Siswa Sekolah Dasar di Pekon Padang Dalom Kecamatan Balik Bukit - Kurniawan, Muhammad; Hidayat, Muhammad Farid; Muslikah, Aliyah; Pratiwi, Nathania; Sari, Dita Indah (Civiliza Publishing, 2024)
Bullying is a prevalent issue in elementary schools that can have severe psychological and social impacts on students. This study aims to evaluate the effectiveness of a localized anti-bullying education program implemented in an elementary school in Pekon Padang Dalom, Balik Bukit District. A descriptive qualitative approach was used, employing in-depth interviews, participant observation, and document analysis to collect data. The findings reveal that interactive and participatory educational methods, such as group discussions and role-playing, significantly enhanced students' understanding of various forms of bullying and preventive measures. The program also led to positive behavioral changes among students, who showed increased courage and proactive behavior in identifying and reporting bullying incidents. However, challenges were noted in the implementation process, particularly resistance from some teachers and parents who preferred traditional teaching methods. These results underscore the importance of adaptive and context-sensitive educational strategies that involve the entire school community. The study suggests the need for further research to develop more inclusive and sustainable anti-bullying intervention models tailored to diverse school environments.